External Cesium-137 doses to humans from soil influenced by the Fukushima and Chernobyl nuclear power plants accidents: a comparative study - Wai, Ka-Ming (Sci Rep, 2020)
External exposure to gamma-photon irradiation from soil contamination due to nuclear power plant (NPP) accidents has significant contribution to human radiation exposure in the proximity of the NPP. Detailed absorbed doses in human organs are rarely reported in the literature. We applied the Monte Carlo Neutron Particle (MCNP) transport code to calculate and compare the absorbed doses in different human organs. The absorbed doses by gamma-photon radiation were from cesium-137 ((137)Cs) in soil contaminated by the two major NPP accidents. More serious and wide-spread impacts of the Chernobyl NPP accident on soil contamination in Ukraine, Belarus, Russia and countries as far as Sweden and Greece were due to the inland location, radiative plume transport pathway and high (137)Cs emission strength (9 times the Fukushima emission). Based on our MCNP calculations, the largest absorbed dose was found in skin. The maximum calculated external (137)Cs annual effective dose received from the Chernobyl accident was 10 times higher relative to the Fukushima accident. Our calculated effective doses at various influenced areas were comparable to those available in the literature. The calculated annual effective doses at areas near the Fukushima and Chernobyl NPPs exceeded the ICRP recommendation of 1 mSv yr(−1).